The Effect of Field Trip Activities for Marine Engineering Cadets on KNL MH Thamrin in Supporting Practical Learning for Sea Internship Preparation - Jarot Delta Susanto; Manurung, Markus Yando; Simanjuntak, P. Dwikora (Meteor STIP Marunda, 2023)
Field trips are a teaching method carried out by taking cadets to a specific location or site outside the classroom. For example, the field trip aboard the KNL MH Thamrin is a practical learning activity aimed at studying and observing all of the ship’s equipment and machinery firsthand, while also providing an introduction (familiarization) to life aboard a ship in preparation for the maritime work practice (Prala) in the 5th and 6th semesters. Prala provides cadets with the opportunity to apply the knowledge they have acquired on campus, demonstrating the relevance between the theory learned during lectures and practical application. Additionally, Prala helps strengthen collaborative relationships between the university and shipping companies. It can also serve as a promotional tool for the institution with potential employers. Complaints from shipping companies regarding cadets’ readiness during their sea training, coupled with the suboptimal implementation of the Field Trip for engineering cadets at KNL MH Thamrin each semester, form the core issues addressed in this study. The objective of this study is to determine whether there is a relationship between the engineering department’s student field trips and the readiness of engineering students during their sea training, as well as the extent of this influence. A quantitative research method was employed, utilizing a questionnaire distributed to 70 third-semester cadets in the Engineering Department who had already completed their field trips. Data analysis was conducted using IBM SPSS version 27.0.1, and the interpretation of the results serves as evaluation material and feedback for STIP to enhance cadet readiness in preparation for their sea training.